Study on Collaborative Creativity Learning Models and Gender on Students' Creative Thinking Skills - Malik, Adam; Prihatini, Sri; Agustina, Rena Denya (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
This study aims to determine the effect of the Collaborative Creativity (CC) learning model on students’ creative thinking skills on simple harmonic vibration material. We also examine the different responses by gender. This quantitative study used a quasi-experimental method with a nonequivalent pretest-posttest control group design. The sample used in this study was grade 10th, consisting of 32 students as the experimental class, and 30 as a control class. The research instrument used was a test of creative thinking skills. The results showed the average N-gain in the experimental class was 0.73 with a very high interpretation, and the control class was 0.32 with a moderate. The results of hypothesis testing using the two-way ANOVA test show a sig < 0.05, which means that the learning model influences students’ creative thinking skills. In addition, the CC learning model was also comfort to use by gender which statistical analysis prove the sig > 0.05, which means that there is no gender effect on students’ creative thinking skills. Thus the Collaborative Creativity (CC) learning model can be used as an alternative to improve students’ creative thinking skills on simple harmonic vibration material.